Essentials of spinal cord injury basic research to clinical practice - Fehlings, Michael (Thieme, 2013)
Essentials of Spinal Cord Injury is written for the spinal cord injury (SCI) team and reflects the multidisciplinary nature of treating patients with SCI. It integrates emerging medical and surgical approaches to SCI with neuroanatomy, neurophysiology, neuroimaging, neuroplasticity, and cellular transplantation. This comprehensive yet concise reference will enable neurosurgeons, orthopedic surgeons, neurologists, and allied health professionals caring for SCI patients to translate research results into patient care. It is also an excellent resource for those preparing for the board exam in SCI medicine.